Activist Public Relations in Heritage Preservation: Prefigurative Practices and Affective Publics in Lasem, Indonesia - Ana Mariani; Saudah Saudah; Danu Prasetyo (Jogjakarta Communication Conference (JCC), 2026)
This study reconceptualizes public relations (PR) as practice by analyzing how communicative processes in Lasem, Indonesia are embedded in community-based heritage preservation, operating as enacted, relational, and activist practices rather than as representational and campaign-oriented functions. It explores how prefigurative practices and affective digital mobilization sustain heritage while strengthening Lasem’s reputation as a heritage city (Kota Pusaka). Using a qualitative case study, data were collected through interviews with community actors, academics, media activist, tourism entrepreneurs, young digital communicators and visitors, complemented by participant observation and digital content analysis. Findings show that heritage communication operates through embodied enactment, narrative legitimacy, affective circulation, and micropolitical negotiation. Communication is embedded in everyday practice rather than promotional strategy. Prefigurative practices generate authenticity and symbolic legitimacy, while tourists amplify narratives through digital storytelling, forming affective publics that enhance visibility and credibility. This study extends activist PR beyond campaigns, integrates prefiguration into communication theory, and highlights affective publics in shaping place-based reputation.